Ads Block Management System Using Open Virtual Private Network on Ubuntu Operating System - Syahputra, Edy Rahman; Oktaviana Sembing, Boni; Rafika Dewi, Arie; Hasdiana, H; Maulana, Halim (International Journal of Engineering and Technology, 2018)
In internet, an ad is something that able to be avoided when opening a web page. At this time many internet based businesses rely on advertising for their income. However, users are dissatisfied with the presence of ads on websites they visit, since the size of the ad data is often proportional to the actual content ads. This impacts not only on loading web pages and may lead to a file that may potentially be a carrier of the virus and may damage the operating system of the visitor. A system that can overcome the annoying ads will be needed by the user for the convenience of users in using the internet media. To overcome this will be built a system using the pi-hole and Ubuntu operating systemÂ